Lycopodium clavatum Linnaeus var. megastachyon Fernald & Bissell. - Collecte 18038. - Natashquan. - Marie-Victorin, Frère; Rolland-Germain, Frère (1924)
Habitat : Sur le sable pur des dunes sud de l'estuaire, très luxuriant dans les dépressions et à demi-immergé dans le sable